Alterations in blood pressure, antioxidant status and caspase 8expression in cobalt chloride-induced cardio-renal dysfunction arereversed by Ocimum gratissimum and gallic acid in Wistar rats (2016)
The protective abilities of the chloroform extract of Ocimum gratissimum (COG) and gallic acid againstcobalt chloride (CoCl2) − induced cardiac and renal toxicity were evaluated. Rats were exposed to CoCl2(350 ppm) for 7 days, either alone, or in combination with COG (100 and 200 mg/kg) or gallic acid(120 mg/kg). CoCl2given alone, caused significant increases (p < 0.05) in oxidative stress parameters(hydrogen peroxide, H2O2and malondialdehyde, MDA) and increased expression of the apoptotic initia-tor caspase 8 in the heart and kidneys. There was significant reduction (p < 0.05) in reduced glutathione(GSH) in cardiac and renal tissues; reduction in superoxide dismutase (SOD) activity in the kidneys andadaptive increases in Glutathione S-transferase (GST) and catalase (CAT). CoCl2also produced signifi-cant reduction (p < 0.05) in systolic (SBP), diastolic (DBP) and mean arterial (MAP) blood pressures. OralCOG and gallic acid treatment significantly reduced (p < 0.05) the levels of H2O2and MDA; with reducedexpression of caspase 8 and restoration of GSH levels, GPx, SOD and CAT activities, howbeit, to varyingdegrees in the heart and kidneys. COG (200 mg/kg) was most effective in restoring the blood pressures inthe rats to near control levels. CoCl2-induced histopathological lesions including myocardial infarctionand inflammation and renal tubular necrosis and inflammation were effectively ameliorated by the treat-ments administered. This study provides evidence for the protective roles of O. gratissimum and gallicacid by modulation of CoCl2-induced alterations in blood pressure, antioxidant status and pro-apoptoticcaspase 8 in Wistar rats.